Learn more about

Refine search

Results (displaying matches 1-50 of 97) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
7662.b.45972.1 7662.b \(y^2 + (x^3 + 1)y = -2x^4 + x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 2
9426.a.509004.1 9426.a \(y^2 + (x^3 + 1)y = 3x^3 + 4x^2 + x\) $\mathrm{USp}(4)$ 2
12330.a.73980.1 12330.a \(y^2 + (x^3 + x^2 + x)y = 2x^3 - 3x + 1\) $\mathrm{USp}(4)$ 2
14394.a.259092.1 14394.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + 3x^2 + 3x\) $\mathrm{USp}(4)$ 2
16824.a.403776.1 16824.a \(y^2 + (x^3 + x)y = x^5 + 3x^2 + 3x + 1\) $\mathrm{USp}(4)$ 2
28542.c.171252.1 28542.c \(y^2 + (x^3 + x^2 + x)y = x^4 + 2x^3 - x^2 - 2x\) $\mathrm{USp}(4)$ 2
33336.a.800064.1 33336.a \(y^2 + (x + 1)y = x^6 - 2x^5 - 2x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ 2
35544.a.853056.1 35544.a \(y^2 + (x + 1)y = x^6 + x^4 - 2x^2\) $\mathrm{USp}(4)$ 2
38466.a.692388.1 38466.a \(y^2 + (x^2 + x + 1)y = 6x^5 + 9x^4 - 4x^2 - x\) $\mathrm{USp}(4)$ 2
40152.a.963648.1 40152.a \(y^2 + (x + 1)y = x^6 + 4x^5 + 3x^4\) $\mathrm{USp}(4)$ 2
83999.a.83999.1 83999.a \(y^2 + (x^3 + 1)y = 3x^5 + 9x^4 + 8x^3 - 2x\) $\mathrm{USp}(4)$ 3
91771.a.91771.1 91771.a \(y^2 + y = x^5 + x^4 - x^2 - x\) $\mathrm{USp}(4)$ 3
94961.a.94961.1 94961.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 - 3x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 3
125237.a.125237.1 125237.a \(y^2 + y = x^5 - x^4 - 3x^3 + x^2 + 2x\) $\mathrm{USp}(4)$ 3
140615.a.703075.1 140615.a \(y^2 + y = x^5 + 2x^4 - 3x^3 + x^2 - x\) $\mathrm{USp}(4)$ 3
141991.b.141991.1 141991.b \(y^2 + (x^2 + x + 1)y = x^5 - 2x^4 - 2x^3 + x^2\) $\mathrm{USp}(4)$ 3
143313.a.429939.1 143313.a \(y^2 + x^3y = x^5 - 5x^3 - 5x^2 + 5x + 6\) $\mathrm{USp}(4)$ 3
143482.a.286964.1 143482.a \(y^2 + (x + 1)y = x^6 + x^5 - 2x^4 - x^3 + x^2\) $\mathrm{USp}(4)$ 3
143849.a.143849.1 143849.a \(y^2 + (x^2 + x + 1)y = -x^5 + 3x^4 - 9x^2 + x + 6\) $\mathrm{USp}(4)$ 3
144203.a.144203.1 144203.a \(y^2 + y = x^5 - 2x^4 + x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 3
146594.a.293188.1 146594.a \(y^2 + xy = x^5 + 3x^4 - x^3 - 7x^2 + 4\) $\mathrm{USp}(4)$ 3
150443.a.150443.1 150443.a \(y^2 + y = x^5 - 2x^4 - x^3 + 2x^2\) $\mathrm{USp}(4)$ 3
151507.a.151507.1 151507.a \(y^2 + (x^2 + x + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 3
153499.a.153499.1 153499.a \(y^2 + (x^2 + x + 1)y = x^5 - 4x^3 - x^2 + 2x\) $\mathrm{USp}(4)$ 3
157137.a.471411.1 157137.a \(y^2 + (x^3 + 1)y = 2x^3 - 5x^2 + 2x\) $\mathrm{USp}(4)$ 3
159482.a.318964.1 159482.a \(y^2 + xy = x^5 + x^4 + x^3 + x^2 + x + 1\) $\mathrm{USp}(4)$ 3
160507.a.160507.1 160507.a \(y^2 + y = x^5 + 2x^4 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 3
164326.a.328652.1 164326.a \(y^2 + (x^3 + 1)y = 2x^4 + x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
166319.a.166319.1 166319.a \(y^2 + xy = x^5 - x^3 - x^2 + 1\) $\mathrm{USp}(4)$ 3
168328.a.336656.1 168328.a \(y^2 + (x^3 + x)y = x^5 - x^4 - x^3 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 3
183902.a.367804.1 183902.a \(y^2 + xy = x^5 - 6x^3 - x^2 + 8x + 4\) $\mathrm{USp}(4)$ 3
184029.a.552087.1 184029.a \(y^2 + (x^2 + x + 1)y = x^5 + 3x^4 - 3x^3 - 3x^2\) $\mathrm{USp}(4)$ 3
191872.a.383744.1 191872.a \(y^2 + y = 2x^5 + x^4 - x^3\) $\mathrm{USp}(4)$ 3
197317.a.197317.1 197317.a \(y^2 + y = x^5 - 3x^4 - x^3 + 7x^2 - 2x\) $\mathrm{USp}(4)$ 3
206111.a.206111.1 206111.a \(y^2 + (x^3 + x^2 + x)y = 3x^4 + 3x^3 - x^2 - x\) $\mathrm{USp}(4)$ 3
209889.a.629667.1 209889.a \(y^2 + (x^3 + x^2 + x)y = 2x^4 + 2x^3 + x^2 - x\) $\mathrm{USp}(4)$ 3
215851.a.215851.1 215851.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 - 4x^3 - x^2 + x\) $\mathrm{USp}(4)$ 3
216423.a.649269.1 216423.a \(y^2 + y = x^5 - 8x^3 + 10x^2 - 3x\) $\mathrm{USp}(4)$ 3
225411.a.676233.1 225411.a \(y^2 + (x^3 + 1)y = x^5 - 5x^3 + x^2 + 2x\) $\mathrm{USp}(4)$ 3
226133.a.226133.1 226133.a \(y^2 + y = x^5 + 2x^4 - 6x^3 + 4x^2 - x\) $\mathrm{USp}(4)$ 3
233138.a.466276.1 233138.a \(y^2 + (x^2 + x + 1)y = 2x^5 - x^4 - 3x^3\) $\mathrm{USp}(4)$ 3
233344.a.466688.1 233344.a \(y^2 + y = 2x^5 - x^4 - 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
235606.a.471212.1 235606.a \(y^2 + (x + 1)y = x^6 - x^5 + x^4 - 2x^2\) $\mathrm{USp}(4)$ 3
249362.a.498724.1 249362.a \(y^2 + (x^2 + x + 1)y = 2x^5 - 9x^4 + 9x^3 - 2x\) $\mathrm{USp}(4)$ 3
249478.a.498956.1 249478.a \(y^2 + (x^2 + 1)y = 2x^5 + 5x^4 - 5x^2 + x\) $\mathrm{USp}(4)$ 3
251578.a.503156.1 251578.a \(y^2 + xy = x^6 - x^5 - 2x^4 + 3x^3 + x^2 - 2x\) $\mathrm{USp}(4)$ 3
252040.b.504080.1 252040.b \(y^2 + (x + 1)y = -2x^5 + 3x^4 + 6x^3 + 2x^2\) $\mathrm{USp}(4)$ 3
253832.a.507664.1 253832.a \(y^2 + (x^3 + x^2)y = -2x^4 + 7x^2 - 10x + 4\) $\mathrm{USp}(4)$ 3
254848.b.509696.1 254848.b \(y^2 + y = 2x^5 - 7x^4 + 5x^3 + 2x^2\) $\mathrm{USp}(4)$ 3
261357.a.784071.1 261357.a \(y^2 + (x^2 + x + 1)y = x^5 - 6x^3 - 3x^2 + 6x + 6\) $\mathrm{USp}(4)$ 3
Next

Download all search results for